(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2005)
Literature data about several debatable questions on present classification of coprinoid mushrooms are discussed. Phylogenetical studies with using molecular methods of genetic analysis of the restriction site DNA, brought out polyphyletics of the traditional genus Coprinus. As a result, the species of genus Coprinus are suggested to divide into four genera (clades) which refer to two families: Agaricaceae and Psathyrellaceae. The family Agaricaceae includes the genus Coprinus s. str., with type species C. comatus, and family Psathyrellaceae: genera Coprinellus, Coprinopsis and Parasola, as well as newly studied species of genera Psathyrella, Lacrymaria Pat. and the main part of former coprinoid mushrooms.